Advances in Cryptology -- ASIACRYPT 2019 : 25th International Conference on the Theory and Application of Cryptology and Information Security, Kobe, Japan, December 8-12, 2019, Proceedings.: 25th International Conference on the Theory and Application of Cryptology and Information Security, Kobe, Japan, December 8-12, 2019, Proceedings. Part I (2019) - Unknown
No abstract available